Exploring strategic priorities for regional agricultural research and development investments in southern Africa - Johnson, Michael E.; Benin, Samuel; You, Liangzhi; Diao, Xinshen; Chilonda, Pius; Kennedy, Adam (International Food Policy Research Institute, 2014)
An in-depth quantitative analysis is undertaken in this paper to assist the Southern African Development Community (SADC) Secretariat, member countries, and development partners in setting future regional investment priorities for agricultural research and development in the SADC region. A primary goal of this work was to identify a range of agricultural research priorities for achieving sector productivity and overall economic growth in southern Africa, at both the country and regional levels. This is accomplished by adopting an integrated modeling framework that combines a disaggregated spatial analytical model with an economywide multimarket model developed specifically for the region.